PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) OLEH PT. KARIMUN GRANITE DI DESA PASIR PANJANG KABUPATEN KARIMUN BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This research is entitled Implementation of Corporate Social Responsibility (CSR) by PT. Karimun Granite in Pasir Panjang Village, Karimun Regency Based on Law Number 40 of 2007 concerning Limited Liability Companies. The purpose of this study was to determine the implementation of Corporate Social Responsibility by PT Karimun Granite Pasir Panjang Village, Karimun Regency and also to determine the efforts that must be made by PT. Karimun Granite in the implementation of Corporate Social Responsibility can improve the socio-economic community.This type of research is empirical juridical research or sociological legal research, namely a research approach that emphasizes the legal aspects regarding the subject matter to be discussed, associated with the reality in the field. This research was conducted in Pasir Panjang Village, namely PT. karimun Granite, while the sample population is all parties related to the problem under study. Sources of data used are primary data and secondary data, data collection techniques in this study are questionnaires, interviews and literature review.In the results of research problems there are two main things that can be concluded. First, the Implementation of Corporate Social Responsibility in PT. Karimun Granite has not been implemented optimally as regulated in Law Number 40 of 2007 concerning Limited Liability Companies and Karimun Regency Government Regulation Number 8 of 2016 concerning Corporate Social Responsibility. The second effort that can be done by PT. Karimun Granite in the Implementation of Corporate Social Responsibility Can Improve the Socio-Economic of the Community, namely bridging community efforts and training for the community, implementing scholarship programs, and establishing health clinics.Keywords: Implementation – Corporate - Social – Responsibility - Karimun